A green approach for A3-coupling reactions: an experimental and theoretical study on NHC silver and gold catalysts. (23rd September 2021) - Costabile, Chiara; Mariconda, Annaluisa; Sirignano, Marco; Crispini, Alessandra; Scarpelli, Francesca; Longo, Pasquale
Abstract : N-heterocyclic carbene silver and gold complexes active in A 3 -coupling (aldehyde–alkyne–amine) reactions in green conditions. Abstract : The synthesis of propargylamines by traditional methods is limited by several drawbacks such as anhydrous conditions, low temperatures and by-products. A 3 -coupling reactions (aldehydes, amines, and alkynes), that involve a catalytic amount of metal complexes, have been recently recognized as a powerful alternative for the synthesis of these important scaffolds. In this paper, four new silver and gold complexes (3a, 4a, 3b and 4b ), bearing N-heterocyclic carbene (NHC) ligands, were tested in A 3 -coupling reactions, combining the use of harmless metals as catalysts with sustainable reaction conditions (neat conditions or water as solvent). NHC silver(i ) and gold(i ) complexes were synthesized and characterized by 1 H and 13 C NMR spectroscopy, ESI-MS and elemental analysis. The molecular structure of the NHC gold(i ) complex 4b was determined by single crystal X-ray diffraction. A comparison of the catalytic behavior in A 3 -coupling reactions among the synthesized complexes disclosed the higher efficiency of gold catalysts. Computational studies shed light on species possibly involved in the catalytic mechanism.